Frequency of Emergency Obstetric Hysterectomy in Patients Presenting at PMC Hospital Nawabshah - Rashida Akbar, Shabana Ramzan, Fozia Unar, Shaista Lashari, Rozina Mujeeb Sahito, Yasmeen Joyo, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of emergency obstetric hysterectomy among pregnant patients presenting at PMC hospital Nawabshah Study Setting: The study was conducted at Obstetrics & Gynecology Department, Peoples Medical College Hospital, Nawabshah. Duration of Study: 10th February, 2021 to 09th August, 2021 Study Design: Descriptive study Methodology: All 82 patients fulfilling the inclusion criteria were included in this study. All hysterectomies were performed after 24 week of gestation. We retrieved the proforma of all cases and emergency obstetric hysterectomy was done. The data were entered and analyzed in SPSS v25.0. Data were stratified for age, parity, socio-economic status, gravida, type of delivery, education status, booking status, BMI, booking status, diabetes mellitus (FBS >126mg/dl) and hypertension (BP >140/90mmHg) to address the effect modifiers. Chi-square test was used post-stratification with a p-value ≤0.05 considered as significant. Results: Total 82 pregnant women of 20-45 years of age having gestational age ≥24 weeks were selected for this study. Mean age of the patients was 31.95±8.06 year. Among 82 women who underwent cesarean section or vaginal delivery, 4 (4.9%) had emergency obstetric hysterectomy. Conclusion: Emergency obstetric hysterectomy is a necessary evil in obstetrics. Although it curtails the future child bearing potential of the woman, in many cases it saves the life of the mother. Most of its morbidity is attributable to its indications and underlying disorders rather than to the procedure itself.